2006
DOI: 10.1017/s0317167100005151
|View full text |Cite
|
Sign up to set email alerts
|

Propionibacterium Acnes Infections After Cranial Neurosurgery

Abstract: THE CANADIAN JOURNAL OF NEUROLOGICAL SCIENCESPropionibacterium acnes (P. acnes) is an anaerobic grampositive bacillus found as a normal component of the bacterial flora of the skin, hair follicles and sebaceous glands. Although the majority of patient isolates are thought to be contaminants, Propionibacterium acnes does cause significant disease in a small subset of patients after neurosurgical procedures. 1Ventriculoperitoneal shunt infections are the most commonly reported type of P. acnes infection in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
12
0
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 19 publications
4
12
0
2
Order By: Relevance
“…In only 2 patients (4.1 %) out of the entire study population no predisposing factors were identified (the patients with infection of the talocrural joint and thoracic empyema), suggesting that these infections might have occurred spontaneously. This observation is in keeping with the marked predominance of reports describing invasive P. acnes infections following neurosurgical and orthopaedic operations in the literature, and the paucity of publications reporting cases with no apparent risk factors [11][12][13][14][15][16][17][18][19][20][21][22][25][26][27].…”
Section: Discussionsupporting
confidence: 79%
“…In only 2 patients (4.1 %) out of the entire study population no predisposing factors were identified (the patients with infection of the talocrural joint and thoracic empyema), suggesting that these infections might have occurred spontaneously. This observation is in keeping with the marked predominance of reports describing invasive P. acnes infections following neurosurgical and orthopaedic operations in the literature, and the paucity of publications reporting cases with no apparent risk factors [11][12][13][14][15][16][17][18][19][20][21][22][25][26][27].…”
Section: Discussionsupporting
confidence: 79%
“…The most common germ in our series was P. acnes. This anaerobic Gram-positive bacillus, found as a normal component of the bacterial flora of the skin, is a common causative germ for infection after craniotomy [25]. The most common infecting organism is reported to be Staphylococcus aureus [10], which was the second most common bacterium in our series.…”
Section: Discussionmentioning
confidence: 61%
“…13 The indolent nature of infection with this pathogen is illustrated by the prolonged duration of symptoms prior to presentation, rarity of fever, usually normal white blood count, no attributable mortality and the significant time lapse from previous neurosurgery to presentation. These findings are similar to previous reports.…”
Section: Discussionmentioning
confidence: 99%